Semiotic Analysis of the Teenage Love Triangle Trilogy as Portrayed in the Taylor Swift Folklore Album; Betty, Cardigan, and August. - Indah Windy Khoerunisa (Passage: Journal of English Language and Literature, 2024)
This article presents the semiotic analysis of the teenage love triangle in the lyrics of Taylor Swift’s songs folklore album entitled Betty, Cardigan, and August by using Barthes' (2013) and Horney’s (2013) psychological concept of love triangle. The research method used a qualitative method with an interpretive approach. The data were acquired by gathering and analyzing the lyrics of these songs to find the meaning of the teenage love triangle supported by journals and relevant data to enforce it. The meanings obtained through this analysis are connotation, denotation, and myth. The findings show that through denotation, connotation, and myth creation, Taylor Swift intertwines these songs to tell a broader story beyond the confines of a love triangle. They become a narrative trilogy that reflects the multifaced nature of relationships, the layers of emotions involved, and the resonance these experiences hold in the broader context of life and love. The characters in these songs portray different facets of human behavior showcasing various neurotic tendencies. This study can contribute positively in understanding how semiotics can be applied to song lyrics, helping us decipher the sign and communicative aspects of music and lyrics.